The Role and Strategy of Islamic Banking Management in Sustainable Financing of the Halal Tourism Industry - Itang; Yama, Arifeen (Best Journal of Administration and Management, 2025)
Islamic banking management is the most rapidly developing part of the Islamic financial system. The significant market share gap between the management of the Islamic banking industry and the real sector (the halal tourism industry) represents a current challenge. Islamic banking management should recognize the opportunities for developing this halal tourism industry and working together in tandem. The halal tourism industry has enormous potential for development. Innovation must be carried out by Islamic financial institutions, especially Islamic banking. In the current digital era, halal tourism industry players and tourists prioritize everything that is practical. The development and improvement of sustainable halal tourism in a country is very important, because the existence of well-maintained and organized halal tourism industry destinations and supported by a strong financial sector will increasingly attract tourists, both domestic and international. The method used in this study is a literature review approach, namely research with a series of activities related to library data collection methods, reading and recording, and processing research materials. From the results of the literature search, it can be seen that Islamic banking management needs to increase branch office access and digital networks in tourist destination areas so that they are easily accessible to tourists. Several other strategies that can be implemented include collaboration with tour and travel companies that will issue tourism products with halal labels, to financially use Islamic banking.